Barium ferrite/epoxy resin nanocomposite system: Fabrication, dielectric, magnetic and hydration studies - A. Kanapitsas; C. Tsonos; G. C. Psarras; S. Kripotou (eXPRESS Polymer Letters)
Composite systems of epoxy resin and barium ferrite nanoparticles have been prepared, and studied varying the content of the inclusions. Morphology of prepared samples has been examined via scanning electron microscopy and X-ray diffraction spectra, while electrical and magnetic properties were investigated by means of broadband dielectric spectroscopy, and magnetization tests respectively. Finally, water vapor sorption measurements were conducted in order to study the water sorption dynamics of the system. Electron microscopy images revealed the successful fabrication of nanocomposites. Dielectric permittivity increases with filler content, while three relaxation processes were detected in the relative spectra. These processes are attributed to interfacial polarization, glass to rubber transition of the matrix, and re-orientation of polar side groups of the polymer’s chain. Magnetization and magnetic saturation increase with magnetic nano-powder content. Nanocomposites absorb a small amount of water, not exceeding 1.7 wt%, regardless filler content, indicating their hydrophobic character.